Solid Waste Management System for Hazardous and Toxic Materials (B3) at Upt. Lambunu 1 Health Center, Bolano District, Parigi Moutong District Central Sulawesi - Permana, Andika Hadi; Rismawati, Nur; Miswan (Yayasan Sinergi Kawula Muda, 2025)
Hazardous and toxic waste is the remainder of business and service facility activities that contain B3. Hazardous and toxic materials are substances, energy and/or other components which, due to their nature, concentration or amount, either directly or indirectly, can pollute and damage the environment, endangering the environment, health and survival of humans and other living creatures. This research is a qualitative study that uses a descriptive case study approach. This approach involves an in-depth investigation of one or several cases that are considered representative. Researchers will collect data through interviews, observations, observations. This research was conducted to describe the management of hazardous and toxic solid waste (B3) at the Lambunu I Community Health Center, Bolano District, Parigi Moutong Regency, Central Sulawesi. The results of research at the Lambunu I Community Health Center found that the collection, sorting and packaging of solid B3 waste that met the requirements for transporting solid B3 waste and temporary shelters (TPS) did not meet the requirements. The conclusion of this research is that the collection, sorting and packaging of solid B3 waste at Lambunu I Community Health Center meets the criteria, while the transportation of solid B3 waste and temporary shelters (TPS) does not comply with the criteria determined by Minister of Health Regulation number 07 of 2019 which does not meet the requirements. This can be realized so that it does not have an impact on health and does not pollute the environment of the health center.